Addressing challenges in vector control: a review of current strategies and the imperative for novel tools in India's combat against vector-borne diseases - Kuldeep Singh; Amit Sharma; Manju Rahi; Sanjeev Kumar Gupta; Gaurav Kumar; Rajendra Baharia; Sam Joy (BMJ Publishing Group, 2024)
Vector-borne diseases (VBDs) exert a substantial burden across the world, especially in tropical countries. Malaria, chikungunya, dengue, visceral leishmaniasis, lymphatic filariasis and Japanese encephalitis are among the public health concerns for India. One of the major pillars for the containment of VBDs is vector control and different tools have been employed for several decades. These range from chemical insecticides used in indoor residual sprays, space sprays, fogging, treated bednets and larvicides to biological control methods such as larvivorus fishes and environmental control and modification measures such as source reduction. However, these methods are increasingly becoming less effective due to several reasons such as insecticide resistance, outdoor biting, behavioural changes in vectors for biting and resting, climate change, movement of population, vector incursion to newer areas and others. It is essential to develop and test new tools for vector control to surmount these challenges. Though focusing on India's public health concerns, the new tools enumerated here can be tested by any country with similar epidemiological and environmental conditions. The promising new vector control tools are insecticide-treated nets with synergist and/or pyrrole chlorfenapyr, alternatives/additions to synthetic pyrethroids like neonicotinoids, clothianidin for indoor residual spray, newer formulations such as Bacillus sphaericus for use in larvicides, attractive toxic sugar baits, especially to curtail outdoor transmission, endectocides like ivermectin for use in animals/humans, insecticidal paints, spatial repellents, insecticide-treated wearables and others. Genetic modification technologies (Sterile Insect Technique/Incompatible Insect Technique/Wolbachia transfection) are also upcoming strategies. Among the six VBDs, India is committed to the elimination of three (malaria, visceral leishmaniasis and lymphatic filariasis) and it will require additional and/or novel tools to overcome the roadblocks in our current journey to the goal of control/elimination of these VBDs.